Optimization of winglet for large commercial aircraft - Tung, How Run. (2009)
Winglet design is one of the important aerodynamics design criterion of modern large commercial aircrafts. Some commercial aircrafts have 10 degree of winglet cant angle while some have 30 to 45 degree of winglet cant angle. In order to understand the rationale behind the design, this work investigates the effect of different winglet cant angle on aerodynamics of the wing and other possible interaction effects with winglet different sweep and toe angles. A wing attached with winglet was designed to operate at low subsonic free stream Mach number of 0.5. The winglet dimension was achieved according to Whitcomb’s[1] winglet. The project is segregated into 3 stages. At stage 1, validation on NACA 0012 airfoil was carried out to obtain suitable parameters for good quality of 3D mesh. At stage 2, the NACA0012 wing with a span of 5 unit chord length was validated. At stage 3, a winglet was attached to the tip of the wing. Parametric study was carried out by varying the cant angle of winglet. By using parametric analysis, the optimum of cant angle of winglet was obtained. The conservation form of FVM (Finite Volume Method) is utilised to discretise the continuity equation, RANS (Reynolds Averaged Navier-Stokes) equations and energy equation. The study adopted commercial code STAR CCM+ compressible viscous solver with hybrid mesh to solve the discretised from of governing equations. Besides, Reichardt Wall Law[2] was adopted as the wall function, to cater all wall y+ treatment on the wall boundary condition. The grid convergence tests were analysed with 2 levels of grids by the Richardson Extrapolation. The comparison of the Mach number contour plot over the wings shows the interference effects between the wing and winglet. The prediction of lift and drag coefficient as well as separation at the junction were overestimated due to incapability of wall function to capture the low Reynolds number effect. Besides, the performance of the winglet was underestimated due to inaccurate computation of wingtip vortex. However, there results were still able to present useful trend on drag polar and lift curve. These have provided valuable insight into the aerodynamics effects of winglet on the performance of the wing.